“You have the right to protect your health”: Perceptions of Secondhand Smoke and Exposure Mitigation Strategies in Low-Income Patients With Heart Disease, San Francisco, 2011–2012 - Brown-Johnson, Cati G. (Prev Chronic Dis, 2016)
We examined the understanding of the harms of secondhand smoke (SHS) exposure among low-income, hospitalized adults with cardiovascular disease. Participants were 15 nonsmokers reporting daily SHS exposure and 15 light or nondaily cigarette smokers. We coded responses from audiotaped semistructured interviews for themes. No participant spontaneously identified heart risks related to SHS exposure. Strategies to avoid SHS included verbal requests to not smoke and physically avoiding smoke; both smokers and nonsmokers prioritized politeness over urgency. Most participants thought a blood test quantifying SHS exposure would be clinically useful. Health education, assertiveness communication training, and protective policies (eg, smoke-free multiunit housing) also were supported.